Trend over time in hepatic fibrosis score in a cohort of type 2 diabetes patients. (January 2018) - Giorda, Carlo Bruno; Forlani, Gabriele; Manti, Roberta; Mazzotti, Arianna; De Cosmo, Salvatore; Rossi, Maria Chiara; Nicolucci, Antonio; Di Bartolo, Paolo; Ceriello, Antonio; Guida, Pietro; Tartaglino, Barbara; Russo, Giuseppina; et al.
Abstract: Aims: The prevalence and progression of hepatic fibrosis and its correlated factors in type 2 diabetes (T2DM) are poorly known. We aimed to define the percentage of T2DM patients who progress to fibrosis and the factors associated with disease progression. Methods: Data from the electronic health records of 1527 patients with diagnosed T2DM and nonalcoholic fatty liver disease (NAFLD), as diagnosed by the Fatty Liver Index, were extracted from the AMD Annals database, which collects data from the Italian network of diabetes clinics. For the main analysis, we evaluated variables associated with Fibrosis 4 [FIB-4] score at baseline and at 3-year follow-up to determine their role in predicting FIB-4 at 3 years and the risk of hepatic fibrosis in T2DM. Results: High-risk of advanced fibrosis was detected in 13.1% of patients at baseline and in 18.1% at 3 years, LDL cholesterol, and body-mass index, correlated negatively with baseline FIB-4 scores, whereas gamma glutamil transerasi correlated positively . The FIB-4 score at 3 years was associated with lower values of baseline renal function, LDL, and BMI; however, the baseline FIB-4 score was the strongest predictor for the FIB-4 score at 3 years. Conclusions: The prevalence of and progression to hepatic fibrosis within 3 years in patients with T2DM is not negligible. Patients with a higher likelihood of liver scarring differ from those with hepatic steatosis. Differently from NAFLD, the FIB-4 score is inversely correlated with insulin resistance and appears to increase independent of classic metabolic factors.